2017
DOI: 10.1007/s10995-017-2346-4
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Prenatal Toxin Exposures and Breastfeeding Duration: A Prospective Cohort Study

Abstract: Introduction Maternal exposure to tobacco smoke is associated with shortened breastfeeding duration, but few studies have examined the effects on breastfeeding outcomes of low level exposures to other toxic chemicals. Moreover, it is unclear if passive smoking is associated with duration of breastfeeding. Our objective was therefore to examine the effect of low-level prenatal exposures to common environmental toxins (tobacco smoke, lead, and phthalates) on breastfeeding exclusivity and duration. Methods We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…A study in the US reported that pregnant women who were exposed to SHS had a significantly shorter time (24.9 weeks) of any breastfeeding duration compared to unexposed pregnant women (29.9 weeks). However, there was no significant association with exclusive breastfeeding duration (2.7 weeks for unexposed vs. 2.1 weeks for exposed) 14 . The purpose of this systematic review to examine the associations between secondhand smoke exposure of nonsmoking women during pregnancy with initiation, prevalence, and duration.…”
Section: Introductionmentioning
confidence: 73%
“…A study in the US reported that pregnant women who were exposed to SHS had a significantly shorter time (24.9 weeks) of any breastfeeding duration compared to unexposed pregnant women (29.9 weeks). However, there was no significant association with exclusive breastfeeding duration (2.7 weeks for unexposed vs. 2.1 weeks for exposed) 14 . The purpose of this systematic review to examine the associations between secondhand smoke exposure of nonsmoking women during pregnancy with initiation, prevalence, and duration.…”
Section: Introductionmentioning
confidence: 73%
“…The rate of elimination depends on the amount of fat a person has (World Health Organisation, ) and, as South Asian populations have more fat mass than Europeans (Deurenberg, Deurenberg‐Yap, & Guiricci, ; Stanfield, Wells, Fewtrell, Frost, & Leon, ), the Pakistani‐origin mothers in our sample may have retained DBPs in their bodies for longer, resulting in greater physiological impact. The compounds may impact breast development and lactation (Bielmeier, Best, & Narotsky, ; Rosen‐Carole et al, ) and may transfer from mother to infant (Batterman, Zhang, Wang, & Franzblau, ), potentially altering the taste and acceptability of breastmilk (Office of Environmental Health Hazard Assessment California Environmental Protection Agency, ). Alternatively, rather than being driven by physiological variation, the observed ethnic differences could be explained by social factors not controlled for, for example, diet and stress (Smith et al, ), or even fertility (although further data exploration shows this to be unlikely [results available on request]).…”
Section: Discussionmentioning
confidence: 99%
“…There has been relatively little research explicitly linking environmental pollutant exposure with breastfeeding outcomes, but chemical compounds have been detected in breastmilk (Stefanidou, Maravelias, & Spiliopoulou, ), some of which are likely to have endocrine disrupting capabilities (Pedersen et al, , p. 72). Hormonal disruption or toxicity can impact mammary gland development during pregnancy (Rosen‐Carole, Auinger, Howard, Brownell, & Lanphear, ) and also the lactation process itself. This is certainly the case for maternal smoking as it has been shown to interfere with the milk ejection reflex, reduce milk output, alter the taste and composition of breastmilk, and suppress infant appetite and increase irritability (Amir, ).…”
Section: Introductionmentioning
confidence: 99%
“…As well as epigenetic effects (Beach et al 2016;Romens et al 2015), our autonomic, neuroendocrine, metabolic and immune systems track environmental information (Cabeza de Baca and Ellis 2017; Vitzthum 2009). Physical and social environments can affect our physiology in similar ways, with for example the chemical compounds in air and water and the experience of parental separation both having endocrine disrupting potential (Alvergne et al 2008;Pedersen et al 2013;Rosen-Carole et al 2017;Toppari and Juul 2010). Coordinating the development of a broad cluster of life historyrelevant traits may depend on consistent environmental information and using childhood environmental conditions to predict adult environmental conditions may only create optimal strategies if the two environments are similar (Alvergne et al 2008; Cabeza de Baca and Ellis 2017; Nettle et al 2011).…”
Section: The Importance Of Socioeconomic Disadvantage and Environmentmentioning
confidence: 99%